IDF-11774 Induces Cell Cycle Arrest and Apoptosis by Inhibiting HIF-1α in Gastric Cancer - Won-Ho Kim; Min-Jee Kim; Jun-O Jin; Peter C. W. Lee (MDPI AG, 2023)
Hypoxia-inducible factor-1 alpha (HIF-1α) is a regulatory factor of intracellular oxygen supersession. The expression or increased activity of HIF-1α is closely related to various human cancers. Previously, IDF-11774 was demonstrated to inhibit HSP70 chaperone activity and suppress the accumulation of HIF-1α. In this study, we aimed to determine the effects of IDF-11774 on gastric cancer cell lines. Treatment with IDF-11774 was found to markedly decrease the proliferation, migration, and invasion of the gastric cancer cell lines. Furthermore, the phosphorylation levels of extracellular signal-regulated kinase 1/2, p38, and Jun N-terminal kinase in the mitogen-activated protein kinase signaling pathways were markedly increased in a dose-dependent manner, ultimately promoting apoptosis via the induction of cell cycle arrest. Our findings indicate that HIF-1α inhibitors are potent drugs for the treatment of gastric cancer.